Outbreak investigation of lead neurotoxicity in children from artificial jewelry cottage industry - Akhil D. Goel; Rohini V. Chowgule (Komiyama Printing Co. Ltd, 2019)
Abstract Background Although lead neurotoxicity is a known phenomenon, it can often be missed at a primary or secondary care level especially if detailed environmental exposure history is missed. Methods This is an outbreak investigation where we observed 15 pediatric cases with neurologic signs and symptoms clustered in a slum area known for an unorganized artificial jewelry industry. Their clinical, biochemical, and epidemiological features were compared with 14 other children from the same region reporting with non-neurological symptoms who were considered as unmatched controls. Results Cases with neurological manifestations had a higher in-house lead smelting activity [OR 7.2 (95% CI 1.4-38.3)] as compared to controls. Toddlers below 3 years of age were more vulnerable to the effects of lead. Conclusion This study emphasizes that many focal sources of lead poisoning still remain especially in the unorganized sector. In cases presenting with unexplained neurotoxicity, specific occupational and environmental inquiry for chemical poisoning, with special consideration for lead, should be actively pursued.